Experimental study on the bearing performance of high pile cap foundation under the coupling effect of scouring and horizontal cyclic loads - Lunliang Duan; Linghao Zhang; Pei Yuan; Yankun Zhang; Duoyin Wang; Meiling Fan; Bo Geng (Soil Dynamics and Earthquake Engineering, 2026)

A bacteriohopanetetrol stereoisomer in Western Pacific oxycline indicates anammox-driven nitrogen loss and warm eddy dynamics - Liqin Duan; Jinming Song; Meiling Yin; Xiaowei Wang; Chuanyu Liu; Jiawei Kan; Zhuoyue Wang; Feng Zhao; Xuegang Li; Huamao Yuan (Geochimica et Cosmochimica Acta, 2026)

Bacteriochlorophyll reveals estuarine hypoxia and anoxygenic photosynthetic carbon fixation - Jiawei Kan; Liqin Duan; Jinming Song; Meiling Yin; Xuegang Li; Xiaoqi Liu; Huamao Yuan; Yingxia Wang (Limnology and Oceanography, 2025)
Bacteriochlorophylls (Bchls) are photosynthetic pigments produced by aerobic anoxygenic photosynthetic bacteria and anoxygenic photosynthetic bacteria. However, the sources, degradation, and influence of redox conditions in marine environments remain unclear. This study investigated the distribution of Bchls in the Changjiang Estuary to evaluate their origins, degradation, and environmental response. Results showed that total bacteriochlorophylls a (T Bchl a ), including bacteriochlorophyll a (Bchl a ) and its degradation product bacteriopheophytin a (Bphe a ), were higher in surface waters than in bottom waters in the inner estuary, where microbial evidence ( Sphingomonadaceae ) identified aerobic anoxygenic photosynthetic bacteria as the dominant source of T Bchl a . In contrast, the outer estuary exhibited elevated T Bchl a in bottom waters, with purple sulfur bacteria ( Chromatiaceae and Ectothiorhodospiraceae ) as the primary contributors. Significant negative correlations between Bphe a concentrations in bottom seawaters and surface sediments and the dissolved oxygen levels in bottom waters, along with a positive correlation between Bphe a in the surface sediments and the salinity difference between bottom and surface seawaters (Δ S ), suggest that Bphe a may serve as a useful indicator of hypoxia and water stratification. The contribution of anoxygenic photosynthetic bacteria to carbon fixation is expected to increase notably, potentially reaching 16% of phytoplankton carbon fixation after 100 years under expanding hypoxia. These findings establish Bchls as reliable indicators of hypoxia and water stratification and provide a framework for reevaluating carbon fixation in global hypoxic coastal systems.

Hypoxia exacerbate the marine ecological risk of arsenic: By stimulating its migration and release at the sediment-water interface - Liqin Duan; Jinming Song; Meiling Yin; Xiaoqi Liu; Xue Liu; Xuegang Li; Huamao Yuan (Water Research, 2025)

Dynamic response of sloping seabed with buried twin pipelines under wave loading - Fan Meiling; Duan Lunliang; Zhou Jianting; Liu Zhuang; Wang Duoyin (Ocean Engineering, 2024)

Vertical variations of bacteriohopanepolyols near the Changjiang Estuary waters: Implications for marine hypoxia and bacterial activities - Meiling Yin; Liqin Duan; Jinming Song; Jiawei Kan; Huamao Yuan; Xuegang Li; Yingxia Wang (Chemical Geology, 2024)

Unraveling seasonal shifts in microbial and geochemical mediated arsenic mobilization at the estuarine sediment-water interface under redox changes - Liqin Duan; Jinming Song; Yuting Zhang; Meiling Yin; Huamao Yuan; Xuegang Li (Science of The Total Environment, 2024)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Exposure to ambient air pollutants is associated with an increased incidence of hyperuricemia: A longitudinal cohort study among Chinese government employees - Lidan Duan; Muyang Zhang; Yuhan Cao; Yuwei Du; Meiling Chen; Rumeng Xue; Minxue Shen; Dan Luo; Shuiyuan Xiao; Yanying Duan (Environmental Research, 2023)

Dose-response relationship of elements with blood lipids and the potential interaction: A cross-sectional study from four areas with different pollution levels in China - Shaoyi Chen; Muyang Zhang; Lidan Duan; Meiling Chen; Yuwei Du; Yuhan Cao; Zhijun Huang; Jia Zhao; Yanying Duan (Journal of Trace Elements in Medicine and Biology, 2023)

Fine genetic mapping confers a major gene controlling leaf shape variation in watermelon - Ming Xu; Meiling Gao; Sikandar Amanullah; Yu Guo; Xiuping Bao; Yaru Duan; Xiujie Liu; Jixiu Liu; Yue Gao; Feishi Luan (Euphytica, 2023)

Numerical study of regular wave-induced oscillatory soil response during the caisson installation - Lunliang Duan; Chenxi Qin; Jianting Zhou; Guangwu Tang; Duoyin Wang; Meiling Fan (Ocean Engineering, 2023)

North-south differences in hypoxia and nitrogen cycle of the East China Sea over the last century indicated by sedimentary bacteriohopanepolyols - Meiling Yin; Jinming Song; Liqin Duan; Huamao Yuan; Xuegang Li; Quancai Peng (Chemical Geology, 2023)

Nonconservative behavior of dissolved molybdenum and its potential role in nitrogen cycling in the Bohai and Yellow Seas - Jinqi Fan; Liqin Duan; Meiling Yin; Huamao Yuan; Xuegang Li (Frontiers in Marine Science, 2022)
Molybdenum plays an important role in marine biological activity, especially in nitrogen cycling as a cofactor for N 2 fixation and nitrate reductase. However, the dissolved Mo (dMo) behavior and its interaction with N cycling in the coastal waters is still unclear. In this study, the dMo concentrations and parameters related to Mo distribution and N cycling in surface and bottom seawaters of the Bohai (BS) and Yellow Seas (YS) were examined. The results showed that dMo concentrations ranged from 36.4 nmol L -1 to 125.0 nmol L -1 , most of which deviated significantly from the conservative line, indicating nonconservative behavior of Mo relative to salinity. The highest dMo concentrations occurring in 36°N section of north of the South YS (SYS), were close to conservative value (105 nmol L -1 ). Significant depletion up to 40-50 nmol L -1 of dMo mainly appeared in the BS, NYS and south of the SYS, suggesting the possible removal of dMo by biological utilization and particle adsorption. Particularly, the increasing dMo concentrations away the Yellow River estuary indicated that freshwater dilution was one of reasons for dMo distributions in the BS. The similar spatial distribution of dMo and dissolved Mn concentrations suggested the possible scavenging by MnO x phases for Mo removal. The negative correlation between dMo and chlorophyll- a (Chl- a ) concentrations in surface seawaters suggested that biological uptake was involved in dMo removal. The depleted dMo in most of sites corresponded with the higher nitrite concentrations, implying the possible involvement of nitrate reduction process. Although the highest N 2 fixation rates and relative abundances of cyanobacteria appeared in 36°N section, corresponding with the conservative dMo, suggesting that Mo may play a minor role in N 2 fixation process there. The ten-folds of relative abundance of bacteria with nitrate reduction function than that with N 2 fixation function suggested that dMo seems to play more important role in nitration reduction than nitrogen fixation in the BS and YS.

Autonomous selfing is altered by pollination in delayed-selfing species Gentianopsis paludosa (Gentianaceae) - Qinzheng Hou; Xiang Zhao; Meiling Duan; Yiping Zhang (Brazilian Journal of Botany, 2022)

First detection of the occurrence and study of the genetic diversity of novel putative kirkoviruses in donkey in China - Panpan Tong; Haifeng Deng; Liya Duan; Meiling Ren; Xiaozhen Song; Hao Wang; Duishanbayi Gulimire; Ling Kuang; Jinxin Xie (Virus Genes, 2022)

Response of the groundwater system in the Guanzhong Basin (central China) to climate change and human activities - Wenke Wang; Zaiyong Zhang; Lei Duan; Zhoufeng Wang; Yaqian Zhao; Qian Zhang; Meiling Dai; Huizhong Liu; Xiaoyan Zheng; Yibo Sun (Hydrogeology Journal, 2018)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)